Evaluating the effect of moisture stress on tomato using non-destructive remote sensing techniques - Mushia, Mahlodi Nicacius (University of Limpopo, 2009)
The aim of this experiment was to evaluate the effect of moisture stress on tomato, using non-destructive remote sensing techniques and agronomic traits under field and greenhouse conditions. Two tomato cultivars Roma VF and Flora Dade were used for the trial. The soil was fertilized optimally for all nutrients to avoid other stresses except water stress; a 2x2 factorial experiment was conducted using two levels of water regimes (stressed vs. control (non-stressed)) having four replicates and two cultivars using a Completely Randomized Design. Pots were put under greenhouse and field conditions. Canopy temperature was measured using an infrared thermometer, NDVI values were recorded using a green seeker hand-held optical sensor unit and stomatal opening were determined using a leaf porometer. Other agronomic traits including days taken for 50% flowering, plant height, number of fruits per plant and fruit yield per plant were recorded. Leaf temperature in stressed plants was high as compared to non-stressed plants, whereas NDVI and stomata conductance values were low. Number of fruits per plant was low; each plant had 4.00 fruits under field conditions and 5.00 fruits per plant under greenhouse conditions as compared to 9.00 fruits under field conditions and 13.00 under greenhouse conditions for non stressed plants. Stressed plants were shorter as compared to non-stressed plants and days taken for 50% flowering were delayed in both cultivars for stressed plants. Stressed plants showed a sign of stress at early stages of plant development. Most of these signs were found on the plants rather than on the fruits, the shape of the main stem of a growing plant was one of the good indicators as it became thin and stringy under stressed conditions. The experiment showed that it is possible to evaluate the effect of moisture stress on tomato by the use of canopy temperature, NDVI, stomatal conductance and agronomic traits.
Thesis (MSC.Agriculture)) --University of Limpopo, 2009.
Keywords: Soil Moisture stress; Tomatoes; 635.6420890826; Tomatoes; Tomatoes -- Breeding